Lumbra camelids, middle valley of Chancay River, Peru - van Dalen Luna, Pieter (2014)
The results of the analysis of the animal bone material from excavations at the archaeological complex of Lumbra (Sector A and B), Season 2012-2013 are presented. As a result of these tests it was determined that the highest percentage of remains are those of camelids (llamas, alpacas), which reveals the great use of these animals not only for food but also for the use of its fiber for textile purposes of bones and artifacts to develop as a means of transportation and communication.